OUTBREAK OF HOSPITAL-AQUIRED INFECTION CAUSED BY MULTIDRUG RESISTANT STRAINS OF K. PNEUMONIAE - Z. V. Grigoryevskaya; I. N. Petukhova; N. V. Dmitrieva (Сибирский онкологический журнал)
The prevalence of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae is increasing globally and is a major clinical concern. Carbapenemase-producing strains (K. Pneumoniaе) can develop resistance to nearly all known antibiotics and in 40-50% of cases lead to death of the patient. Epidemiological studies of outbreaks of infections caused by pathogenic microorganisms are carried out in most clinics of the world. Creation of hospital epidemiology program allows the control of hospital’s infection. In September, 2013, the outbreak of infection caused by MDR strains of K. Pneumoniaе was registered at the N.N. Blokhin Russian Cancer Research Center, and the epidemiologic study was conducted.